The Wiley Handbook of Sustainability in Higher Education Learning and Teaching - Gamage, Kelum A. A.; Gamage, Kelum A. A., 1983-; Gunawardhana, Nanda (Hoboken: Wiley Blackwell, 2022)
"This book provides a reference for the higher education community to embed sustainability in learning and teaching. Sustainable development goals describe key development challenges faced by humans; many higher education institutions are committed to implement sustainability as a part of their learning and teaching delivery strategy, to boost the 2030 Agenda for Sustainable Development adopted by the UN General Assembly. This book explores sustainability in learning and teaching in various disciplines in higher education and offers comprehensive guidance to educators and researchers to implement sustainability in education"--
Includes bibliographical references.
Keywords: Sustainable Development Goals; Education, Higher -- Social aspects; Sustainable development; Educational change